Preparation method of surface small-aperture AGM (Absorbed Glass Mat) separator and product thereof
By performing surface heat treatment on the AGM partition, a multi-layer pore size structure is formed, which solves the problem of insufficient pore structure of the existing AGM partition, and significantly improves its mechanical strength and battery performance.
Patent Information
- Application Number
- CN202410592464.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-05-14
AI Technical Summary
There are problems with the pore structure of the existing AGM partitions, which leads to insufficient maintenance of acid liquid, affecting the cycle life and performance of the battery.
Surface heat treatment technology is used to optimize the surface structure of the AGM partition to form a multi-layered pore size structure, and the pore size in the surface area is significantly smaller than the pore size in the middle area.
The mechanical strength and battery performance of the AGM partition are significantly improved through surface heat treatment, extending the battery cycle life and simplifying the preparation steps.
Smart Images

Figure CN119401053A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of AGM batteries, and in particular relates to a preparation method of an AGM separator with small pores on the surface and a product thereof. Background Art
[0002] AGM batteries are different from general liquid lead-acid batteries, flooded lead-acid batteries and colloidal batteries. Their main feature is that there is a layer of AGM (Absorbed Glass Mat, ultra-fine glass fiber separator) between the plates. This layer of AGM separator can absorb acid and prevent it from overflowing on the one hand, and can regulate the chemical reaction of the lead-acid battery on the other hand. For example, the gaps in the AGM separator are channels for ion migration, which to a certain extent determine the efficiency of the battery reaction; the AGM separator can ensure that the inside of the battery is always under pressure, thereby greatly increasing the cycle life of the lead-acid battery; the AGM separator can provide an oxygen recombination channel, thereby reducing electrolyte loss, and no maintenance is required during the use of the battery. Therefore, balancing the pore channels of the AGM separator is crucial to the final battery performance. However, the existing single-pore structure AGM either has too large pores, which is conducive to acid injection but not to acid retention, or too small pores, which is not conducive to acid injection but conducive to pressure retention. Summary of the invention
[0003] In order to solve the technical problems existing in the prior art, the purpose of the present invention is to provide a method for preparing an AGM separator with small surface pores and a product thereof.
[0004] In order to achieve the above purpose and the above technical effect, the technical solution adopted by the present invention is:
[0005] A method for preparing an AGM separator with small pores on the surface comprises the following steps:
[0006] (1) Slurry preparation:
[0007] The glass fine fibers are mixed with water and then beaten to obtain a uniform slurry;
[0008] (2) Molding:
[0009] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0010] (3) Vacuum drying:
[0011] The AGM separator single-layer structure blank is vacuum dried to obtain a dry AGM single-layer separator blank:
[0012] (4) Surface heat treatment:
[0013] The AGM single-layer separator blank obtained in step (3) is subjected to surface heat treatment;
[0014] (5) Post-processing:
[0015] After cutting and packaging, the finished AGM separator is obtained.
[0016] Furthermore, in step (1), by weight percentage, 60%-100% of glass fine fibers, 0%-20% of short fibers, 0%-20% of organic fibers, and water are mixed, and a uniform slurry is obtained after pulping, mixing, and deslagging.
[0017] Furthermore, by weight percentage, 80%-100% of glass fine fibers, 0%-12% of short fibers, 0%-8% of organic fibers, and water are mixed, and a uniform slurry is obtained after pulping, mixing, and deslagging.
[0018] Furthermore, in step (4), the surface heat treatment temperature is 500-1400° C., the surface heat treatment time is 1-120 s, and the surface heat treatment area is located in the 0-1 mm thickness area of the upper layer of the entire AGM separator.
[0019] Furthermore, the surface heat treatment temperature is 800-1100° C., the surface heat treatment time is 5-60s, and the surface heat treatment area is located in the 0.1-0.5mm thickness area of the upper layer of the entire AGM separator.
[0020] Furthermore, in step (5), the finished AGM separator has a thickness of 0.3 mm to 4 mm, presenting a multi-level pore structure, and the pore size in the surface area is significantly smaller than that in the middle area.
[0021] The present invention also discloses an AGM separator with small surface pores prepared by the method for preparing the AGM separator with small surface pores as described above.
[0022] Furthermore, the AGM separator has a thickness of 0.3 mm to 4 mm and presents a multi-level pore structure, wherein the pore size in the surface area is significantly smaller than that in the middle area.
[0023] Furthermore, the pore size in the surface area is 0.1-10 μm, and the pore size in the middle area is 1-30 μm.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention discloses a preparation method of an AGM separator with small surface pores and a product thereof. The surface structure of the AGM separator is optimized by surface heat treatment to form a multi-level pore structure. The pore size in the surface area is significantly smaller than the pore size in the middle area, so that the mechanical strength of the overall AGM separator is greatly improved, which is beneficial to the improvement of various performances in the battery and the promotion and application of the AGM separator. The overall structure is stable and the preparation steps are simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of a small-pore AGM separator in Example 1 of the present invention before surface heat treatment; wherein, Figure 1 a is a 100-fold SEM image before surface heat treatment. Figure 1 b is a 500-fold SEM image before surface heat treatment;
[0027] Figure 2 This is a SEM image of an AGM separator with small pores on the surface after surface heat treatment according to Example 1 of the present invention; wherein: Figure 1 a is a 100-fold SEM image after surface heat treatment. Figure 1 b is a 500-fold SEM image after surface heat treatment. DETAILED DESCRIPTION
[0028] The present invention is described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0029] A brief summary of one or more aspects is given below to provide a basic understanding of these aspects. This summary is not an exhaustive overview of all conceived aspects, and is neither intended to identify the key or critical elements of all aspects nor to define the scope of any or all aspects. Its only purpose is to give some concepts of one or more aspects in a simplified form as a prelude to a more detailed description that will be given later.
[0030] The present invention discloses a method for preparing an AGM separator with small pores on the surface, comprising the following steps:
[0031] (1) Slurry preparation:
[0032] By weight percentage, 60%-100% of glass fine fibers, 0%-20% of short chopped fibers, 0%-20% of organic fibers, and water are mixed, and a uniform slurry is obtained after pulping, slurry preparation, and slag removal;
[0033] (2) Molding:
[0034] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0035] (3) Vacuum drying:
[0036] The AGM separator single-layer structure blank is vacuum dried to obtain a dry AGM single-layer separator blank:
[0037] (4) Surface heat treatment:
[0038] The AGM single-layer separator blank obtained in step (3) is subjected to surface heat treatment by surface flame baking, infrared heating, laser heating, contact resistance heating or other surface heat treatment methods, the surface heat treatment temperature is 500-1400°C, the surface heat treatment time is 1-120s, and the surface heat treatment area is located in the 0-1mm thickness area of the upper layer of the entire AGM separator. Preferably, the surface heat treatment temperature is 800-1100°C, the surface heat treatment time is 5-60s, and the surface heat treatment area is located in the 0.1-0.5mm thickness area of the upper layer of the entire AGM separator;
[0039] (5) Post-processing:
[0040] After cutting and packaging, the finished AGM separator is obtained, which has a thickness of 0.3mm-4mm and presents a multi-level pore structure. The pore size of the surface area is significantly smaller than that of the middle area. Specifically, the pore size of the surface area is 0.1-10μm, and the pore size of the middle area is 1-30μm.
[0041] In step (1), 80%-100% of glass fine fibers, 0%-12% of short fibers, 0%-8% of organic fibers, and water are mixed by weight, and a uniform slurry is obtained after pulping, mixing, and deslagging.
[0042] The present invention also discloses a method for preparing an AGM separator with small surface pores as described above. The prepared AGM separator has a thickness of 0.3mm-4mm. The surface structure of the AGM separator is optimized by surface heat treatment to form a multi-level pore structure. The pore size of the surface area is significantly smaller than that of the middle area. The pore size of the surface area is 0.1-10μm, and the pore size of the middle area is 1-30μm. The mechanical strength and other properties of the overall AGM separator are greatly improved, which is beneficial to the improvement of its various performances in the battery and the promotion and application of the AGM separator. The overall structure is stable and the preparation steps are simple.
[0043] Example 1
[0044] A method for preparing an AGM separator with small pores on the surface comprises the following steps:
[0045] (1) Slurry preparation:
[0046] By weight percentage, 90% of glass fine fibers with a diameter of 1.5 μm, 10% of short glass fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0047] (2) Molding:
[0048] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0049] (3) Vacuum drying:
[0050] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0051] (4) Surface heat treatment:
[0052] The AGM single-layer separator blank obtained in step (3) is subjected to heat treatment on its surface by infrared heating equipment, and the process parameters are: treatment temperature 900° C., treatment time 40 s, and the surface heat treatment area is located in the 0.3 mm thickness area of the upper layer of the entire AGM separator;
[0053] (5) Post-processing:
[0054] The finished AGM separator is obtained after cutting and packaging. The obtained AGM separator has a double-layer structure with a thickness of 1.5mm. The tensile strength of the overall AGM separator in the machine direction under dry conditions is 0.8KN / m, the elongation at break is 4%, the maximum pore size in the surface area is 5μm, the maximum pore size in the middle area is 20μm, and the overall AGM separator has a 24h acid absorption height of 750mm.
[0055] Example 2
[0056] A method for preparing an AGM separator with small pores on the surface comprises the following steps:
[0057] (1) Slurry preparation:
[0058] By weight percentage, 88% of glass fine fibers with a diameter of 1.5 μm, 6% of short glass fibers, 6% of organic fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0059] (2) Molding:
[0060] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0061] (3) Vacuum drying:
[0062] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0063] (4) Surface heat treatment:
[0064] The AGM single-layer separator blank obtained in step (3) is subjected to heat treatment on its surface by infrared heating equipment, and the process parameters are: treatment temperature 900° C., treatment time 5 s, and the surface heat treatment area is located in the 0.3 mm thickness area of the upper layer of the entire AGM separator;
[0065] (5) Post-processing:
[0066] The finished AGM separator is obtained after cutting and packaging. The obtained AGM separator has a double-layer structure with a thickness of 1.5mm. The tensile strength of the overall AGM separator in the machine direction under dry conditions is 1.2KN / m, the elongation at break is 4%, the maximum pore size in the surface area is 5μm, the maximum pore size in the middle area is 20μm, and the overall AGM separator has a 24h acid absorption height of 700mm.
[0067] The rest is the same as in Example 1.
[0068] Example 3
[0069] A method for preparing an AGM separator with small pores on the surface comprises the following steps:
[0070] (1) Slurry preparation:
[0071] By weight percentage, 88% of glass fine fibers with a diameter of 1.5 μm, 6% of short glass fibers, 6% of organic fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0072] (2) Molding:
[0073] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0074] (3) Vacuum drying:
[0075] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0076] (4) Surface heat treatment:
[0077] The AGM single-layer separator blank obtained in step (3) is subjected to heat treatment on its surface by infrared heating equipment, and the process parameters are: treatment temperature 900° C., treatment time 5 s, and the surface heat treatment area is located in the 0.3 mm thickness area of the upper layer of the entire AGM separator;
[0078] (5) Post-processing:
[0079] The finished AGM separator is obtained after cutting and packaging. The obtained AGM separator has a three-layer structure with a thickness of 1.5mm. The tensile strength of the overall AGM separator in the machine direction under dry conditions is 1.3KN / m, the elongation at break is 4%, the maximum pore size in the surface area is 5μm, the maximum pore size in the middle area is 20μm, and the overall AGM separator has a 24h acid absorption height of 750mm.
[0080] The rest is the same as in Example 1.
[0081] Comparative Example 1
[0082] The difference between this comparative example and Example 1 is that this comparative example does not have a surface heat treatment step, that is, step (4) of Example 1 is omitted.
[0083] The preparation method of the AGM separator of this comparative example comprises the following steps:
[0084] (1) Slurry preparation:
[0085] By weight percentage, 90% of glass fine fibers with a diameter of 1.5 μm, 10% of short glass fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0086] (2) Molding:
[0087] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0088] (3) Vacuum drying:
[0089] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0090] (4) Post-processing:
[0091] The finished AGM separator is obtained after cutting and packaging. The obtained AGM separator is a single-layer structure with a thickness of 1.5mm. Under dry conditions, the tensile strength of the overall AGM separator in the machine direction is 0.5KN / m, the elongation at break is 4%, the maximum pore size is 20μm, and the overall AGM separator 24h acid absorption height is 700mm.
[0092] The rest is the same as in Example 1.
[0093] Comparative Example 2
[0094] A method for preparing an AGM separator comprises the following steps:
[0095] (1) Slurry preparation:
[0096] By weight percentage, 90% of glass fine fibers with a diameter of 1.5 μm, 10% of short glass fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0097] (2) Molding:
[0098] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0099] (3) Vacuum drying:
[0100] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0101] (4) Surface heat treatment:
[0102] The AGM single-layer separator blank obtained in step (3) is subjected to heat treatment on its surface by infrared heating equipment, and the process parameters are: treatment temperature 1500° C., treatment time 100 s, and the surface treatment area is located in the 0.3 mm thickness area of the upper layer of the entire AGM separator;
[0103] (5) Post-processing:
[0104] The finished AGM separator is obtained after cutting and packaging. The obtained AGM separator is a single-layer structure with a thickness of 1.3mm. Under dry conditions, the tensile strength of the overall AGM separator in the machine direction is 0.7KN / m, the elongation at break is 0.2%, the maximum pore size is 1μm, and the overall AGM separator 24h acid absorption height is 500mm.
[0105] The rest is the same as in Example 1.
[0106] Comparative Example 3
[0107] A method for preparing an AGM separator comprises the following steps:
[0108] (1) Slurry preparation:
[0109] By weight percentage, 90% of glass fine fibers with a diameter of 1.5 μm, 10% of short glass fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0110] (2) Molding:
[0111] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0112] (3) Vacuum drying:
[0113] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0114] (4) Surface heat treatment:
[0115] The AGM single-layer separator blank obtained in step (3) is subjected to heat treatment on its surface by infrared heating equipment, and the process parameters are: treatment temperature 400° C., treatment time 100 s, and the surface treatment area is located in the 0.3 mm thickness area of the upper layer of the entire AGM separator;
[0116] (5) Post-processing:
[0117] The finished AGM separator is obtained after cutting and packaging. The obtained AGM separator is a single-layer structure with a thickness of 1.5mm. Under dry conditions, the tensile strength of the overall AGM separator in the machine direction is 0.5KN / m, the elongation at break is 4%, the maximum pore size is 20μm, and the overall AGM separator 24h acid absorption height is 700mm.
[0118] The rest is the same as in Example 1.
[0119] Comparative Example 4
[0120] A method for preparing an AGM separator comprises the following steps:
[0121] (1) Slurry preparation:
[0122] By weight percentage, 90% of glass fine fibers with a diameter of 1.5 μm, 10% of short glass fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0123] (2) Molding:
[0124] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0125] (3) Vacuum drying:
[0126] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0127] (4) Surface heat treatment:
[0128] The AGM single-layer separator blank obtained in step (3) is subjected to heat treatment on its surface by infrared heating equipment, and the process parameters are: treatment temperature 1000° C., treatment time 150 s, and the surface treatment area is located in the 0.3 mm thickness area of the upper layer of the entire AGM separator;
[0129] (5) Post-processing:
[0130] The finished AGM separator is obtained after cutting and packaging. The obtained AGM separator is a single-layer structure with a thickness of 1.4mm. The tensile strength of the overall AGM separator in the machine direction under dry conditions is 0.75KN / m, the elongation at break is 0.5%, the maximum pore size is 2μm, and the overall AGM separator 24h acid absorption height is 600mm.
[0131] The rest is the same as in Example 1.
[0132] Comparative Example 5
[0133] A method for preparing an AGM separator comprises the following steps:
[0134] (1) Slurry preparation:
[0135] By weight percentage, 90% of glass fine fibers with a diameter of 1.5 μm, 10% of short glass fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0136] (2) Molding:
[0137] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0138] (3) Vacuum drying:
[0139] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0140] (4) Surface heat treatment:
[0141] The AGM single-layer separator blank obtained in step (3) is subjected to heat treatment on its surface by infrared heating equipment, and the process parameters are: treatment temperature 1000° C., treatment time 100 s, and the surface treatment area is deep inside the entire AGM separator;
[0142] (5) Post-processing:
[0143] The finished AGM separator is obtained after cutting and packaging. The obtained AGM separator is a single-layer structure with a thickness of 1.4mm. The tensile strength of the overall AGM separator in the machine direction under dry conditions is 0.75KN / m, the elongation at break is 0.5%, the maximum pore size is 2μm, and the overall AGM separator 24h acid absorption height is 600mm.
[0144] The rest is the same as in Example 1.
[0145] Comparative Example 6
[0146] The difference between this comparative example and Example 2 is that this comparative example does not have a surface heat treatment step, that is, step (4) of Example 2 is omitted.
[0147] A method for preparing an AGM separator comprises the following steps:
[0148] (1) Slurry preparation:
[0149] By weight percentage, 88% of glass fine fibers with a diameter of 1.5 μm, 6% of short glass fibers, 6% of organic fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0150] (2) Molding:
[0151] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0152] (3) Vacuum drying:
[0153] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0154] (4) Post-processing:
[0155] The finished AGM separator is obtained after cutting and packaging. The obtained AGM separator is a single-layer structure with a thickness of 1.5mm. The tensile strength of the overall AGM separator in the machine direction under dry conditions is 0.8KN / m, the elongation at break is 4%, the maximum pore size is 20μm, and the overall AGM separator 24h acid absorption height is 550mm.
[0156] The rest is the same as Example 2.
[0157] Comparative Example 7
[0158] A method for preparing an AGM separator comprises the following steps:
[0159] (1) Slurry preparation:
[0160] By weight percentage, 88% of glass fine fibers with a diameter of 1.5 μm, 6% of short glass fibers, 6% of organic fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0161] (2) Molding:
[0162] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0163] (3) Vacuum drying:
[0164] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0165] (4) Surface heat treatment:
[0166] The surface of the AGM single-layer separator blank obtained in step (3) was heat-treated by infrared heating equipment at a treatment temperature of 1500° C. and a treatment time of 100 s. The AGM separator was yellow-black and could no longer be used for subsequent processing.
[0167] The rest is the same as Example 2.
[0168] Comparative Example 8
[0169] A method for preparing an AGM separator comprises the following steps:
[0170] (1) Slurry preparation:
[0171] By weight percentage, 88% of glass fine fibers with a diameter of 1.5 μm, 6% of short glass fibers, 6% of organic fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0172] (2) Molding:
[0173] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0174] (3) Vacuum drying:
[0175] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0176] (4) Surface heat treatment:
[0177] The AGM single-layer separator blank obtained in step (3) is subjected to heat treatment on its surface by infrared heating equipment, and the process parameters are: treatment temperature 400° C., treatment time 100 s, and the surface treatment area is located in the 0.3 mm thickness area of the upper layer of the entire AGM separator;
[0178] (5) Post-processing:
[0179] The finished AGM separator is obtained after cutting and packaging. The obtained AGM separator is a single-layer structure with a thickness of 1.5mm. The tensile strength of the overall AGM separator in the machine direction under dry conditions is 0.6KN / m, the elongation at break is 4%, the maximum pore size is 20μm, and the overall AGM separator has a 24h acid absorption height of 550mm.
[0180] The rest is the same as Example 2.
[0181] Comparative Example 9
[0182] A method for preparing an AGM separator comprises the following steps:
[0183] (1) Slurry preparation:
[0184] By weight percentage, 88% of glass fine fibers with a diameter of 1.5 μm, 6% of short glass fibers, 6% of organic fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0185] (2) Molding:
[0186] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0187] (3) Vacuum drying:
[0188] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0189] (4) Surface heat treatment:
[0190] The surface of the AGM single-layer separator blank obtained in step (3) was heat-treated using an infrared heating device at a temperature of 1000° C. for 150 seconds. The AGM separator was yellow-black and could no longer be processed and used.
[0191] The rest is the same as Example 2.
[0192] Comparative Example 10
[0193] A method for preparing an AGM separator comprises the following steps:
[0194] (1) Slurry preparation:
[0195] By weight percentage, 88% of glass fine fibers with a diameter of 1.5 μm, 6% of short glass fibers, 6% of organic fibers, and an appropriate amount of water are mixed, and pulped, and a uniform pulp is obtained after removing slag through a filter;
[0196] (2) Molding:
[0197] The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator;
[0198] (3) Vacuum drying:
[0199] The AGM separator single-layer structure blank is vacuum dehydrated and dried, and the weight is controlled at 250gsm to obtain a dry AGM single-layer separator blank:
[0200] (4) Surface heat treatment:
[0201] The surface of the AGM single-layer partition blank obtained in step (3) is heat-treated using an infrared heating device at a treatment temperature of 1000°C and a treatment time of 100s. The surface treatment area penetrates deep into the entire AGM partition. The AGM partition is yellow-black and cannot be used for subsequent processing.
[0202] The rest is the same as Example 2.
[0203] Figure 1 This is a SEM image of a small-pore AGM separator in Example 1 of the present invention before surface heat treatment; wherein, Figure 1 a is a 100-fold SEM image before surface heat treatment. Figure 1 b is a 500-fold SEM image before surface heat treatment.
[0204] Figure 2This is a SEM image of an AGM separator with small pores on the surface after surface heat treatment according to Example 1 of the present invention; wherein: Figure 1 a is a 100-fold SEM image after surface heat treatment. Figure 1 b is a 500-fold SEM image after surface heat treatment.
[0205] Depend on Figure 1-2 It can be seen that compared with the AGM separator that has not been subjected to surface heat treatment, the surface structure of the AGM separator is optimized after surface heat treatment, and the pores on the surface are shrunk, which is beneficial to improving the strength of the AGM and increasing the 24-hour acid absorption value.
[0206] The AGM separators obtained in Examples 1-3 and Comparative Examples 1-10 were respectively assembled and tested in batteries at a pressure of 50 kPa, and their performance and final battery effects are summarized in Table 1-2 below.
[0207] Table 1
[0208]
[0209] It can be seen from the above that the AGM separator of Example 1 has excellent performance in all aspects (tensile strength, acid absorption strength, processing efficiency, cycle performance, etc.). Compared with Example 1, Example 1 has no surface heat treatment, the surface heat treatment temperature of Example 2 is too high, the surface heat treatment temperature of Example 3 is too low, the surface heat treatment time of Example 4 is too long, and the surface heat treatment area of Example 5 is too large, resulting in the tensile strength, acid absorption strength and cycle performance of Examples 1-5 being lower than those of Example 1. This shows that the surface heat treatment step of the present invention has an important influence on the performance improvement of the AGM separator, which is beneficial to improving the AGM strength and the 24-hour acid absorption value, and the surface heat treatment process parameters, including the treatment temperature, treatment time and treatment area, will affect the performance of the AGM separator. Exceeding the process parameter range recorded in the present invention will reduce the performance of the AGM separator. Only by adopting the process parameters recorded in the present invention can the performance of the AGM separator be improved. At the same time, it was also found that since Comparative Example 1 had no surface heat treatment and the surface heat treatment of Comparative Example 3 did not achieve the desired effect (the temperature was too low), the elongation at break of the two was basically the same (4%). After the surface heat treatment optimization of Example 1, the elongation at break remained unchanged, but at the same time, the tensile strength, acid absorption strength, processing efficiency, cycle performance and other properties were significantly improved. However, since the surface heat treatment of Comparative Examples 2, 4, and 5 was excessive (the temperature was too high, the time was too long, and the area was too large), the elongation at break was reduced, and other properties were also reduced.
[0210] Table 2
[0211]
[0212]
[0213] It can be seen from the above that, compared with Examples 2-3, Example 6 has no surface heat treatment, Example 7 has a surface heat treatment temperature that is too high, Example 8 has a surface heat treatment temperature that is too low, Example 9 has a surface heat treatment time that is too long, and Example 10 has a surface heat treatment area that is too large, resulting in the tensile strength, acid absorption strength, and cycle performance of Examples 6-10 being lower than those of Examples 2-3. This shows that the surface heat treatment step of the present invention has an important influence on the performance improvement of the AGM separator, and the surface heat treatment process parameters, including the treatment temperature, treatment time, and treatment area, will affect the performance of the AGM separator. Exceeding the process parameter range recorded in the present invention will reduce the performance of the AGM separator, and may even cause the AGM separator to be yellow-black and unable to be used for subsequent processing. Only by adopting the process parameters recorded in the present invention can the performance of the AGM separator be improved. Comparing Comparative Examples 2 and 9, it can be seen that under the same heat treatment conditions, reducing the amount of fine glass fiber and increasing the amount of chopped glass fiber and organic fiber will cause the AGM separator to be yellow-black and can no longer be used for subsequent processing, indicating that the compounding ratio of fine glass fiber, chopped glass fiber and organic fiber has an important influence on the preparation of the AGM separator required by the present invention. The amount of fine glass fiber, chopped glass fiber and organic fiber and the surface heat treatment process parameters are conducive to obtaining the AGM separator required by the present invention. It is also found that the AGM separators of Comparative Examples 1-10 are single-layered, which is caused by the poor surface heat treatment effect, while the AGM separators of Examples 1-2 are double-layered, and the AGM separators of Example 3 are three-layered, all of which can maintain part of the original macroporous structure, and increase the surface structure of small pores after surface heat treatment, which helps to improve the various performances of the AGM separator.
[0214] Parts or structures not specifically described in the present invention may adopt existing technologies or existing products and will not be described in detail here.
[0215] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing an AGM separator with small pore size on the surface, characterized in that: The following steps are involved: (1) Slurry preparation: The glass fine fibers are mixed with water and then beaten to obtain a uniform slurry; (2) Molding: The slurry is input into a molding machine to obtain a single-layer structure blank of an AGM separator; (3) Vacuum drying: The AGM separator single-layer structure blank is vacuum dried to obtain a dry AGM single-layer separator blank: (4) Surface heat treatment: The AGM single-layer separator blank obtained in step (3) is subjected to surface heat treatment; (5) Post-processing: After cutting and packaging, the finished AGM separator is obtained.
2. The method for preparing an AGM separator with small surface pores according to claim 1, characterized in that: In step (1), by weight percentage, 60%-100% of glass fine fibers, 0%-20% of short fibers, 0%-20% of organic fibers, and water are mixed, and a uniform slurry is obtained after pulping, mixing, and deslagging.
3. The method for preparing an AGM separator with small surface pores according to claim 2, characterized in that: According to weight percentage, 80%-100% of glass fine fiber, 0%-12% of short-cut fiber, 0%-8% of organic fiber and water are mixed, and a uniform slurry is obtained after pulping, slurry preparation and slag removal.
4. The method for preparing an AGM separator with small surface pores according to claim 1, characterized in that: In step (4), the surface heat treatment temperature is 500-1400° C., the surface heat treatment time is 1-120 s, and the surface heat treatment area is located in the 0-1 mm thickness area of the upper layer of the entire AGM separator.
5. The method for preparing an AGM separator with small surface pores according to claim 4, characterized in that: The surface heat treatment temperature is 800-1100°C, the surface heat treatment time is 5-60s, and the surface heat treatment area is located in the 0.1-0.5mm thickness area of the upper layer of the entire AGM separator.
6. The method for preparing an AGM separator with small surface pores according to claim 1, characterized in that: In step (5), the finished AGM separator has a thickness of 0.3 mm to 4 mm and presents a multi-level pore structure, with the pore size in the surface area being significantly smaller than that in the middle area.
7. The method for preparing an AGM separator with small surface pores according to claim 6, characterized in that: The pore size in the surface area is 0.1-10 μm, and the pore size in the middle area is 1-30 μm.
8. An AGM separator with small surface pores prepared according to the method for preparing an AGM separator with small surface pores according to any one of claims 1 to 7.
9. The AGM separator with small pore size on the surface according to claim 8, characterized in that: The AGM separator has a thickness of 0.3 mm to 4 mm and presents a multi-level pore structure, wherein the pore size in the surface area is significantly smaller than that in the middle area.
10. The AGM separator with small surface pores according to claim 9, characterized in that: The pore size in the surface area is 0.1-10 μm, and the pore size in the middle area is 1-30 μm.
Citation Information
Patent Citations
A preparation method of an AGM separator with high strength and low resistivity
CN109192905A
preparation method of an AGM separator with low resistivity
CN109273642A
Lead-acid battery
CN201845836U
Separator for storage battery
JP1987252063A
Resin sheet having porous layered structure useful as electrode separator for electric cells
US3967978A